EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MENDUKUNG PEMBELAJARAN DI SEKOLAH MENENGAH ATAS (SMA) SEKOLAH SUKMA BANGSA KABUPATEN SIGI - Nurmansaleh, Erik; Hardian, Dafyar Eliadi; Shadiq, Teuku Fajar (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the effectiveness of the management of School Operational Assistance (BOS) funds in supporting learning at Sukma Bangsa Senior High School in Sigi Regency. The background of the study is based on the importance of transparency, accountability, and optimization of BOS fund use as a government effort to improve the quality of education, particularly in post-disaster areas such as Sigi Regency. The main focus of the study is to evaluate the planning, management, and allocation processes of BOS funds and to assess their impact on the quality of learning in schools. The research questions include how BOS funds are managed, the extent to which funds are allocated for operational learning needs, the impact of management on educational quality, and the factors influencing their effectiveness. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation, involving the principal, treasurer, teachers, and the school committee as key informants. Data analysis was conducted thematically based on the categories of planning, implementation, supervision, and learning outcomes. The results indicate that BOS fund management at Sukma Bangsa Senior High School in Sigi has been carried out transparently, efficiently, and accountably in accordance with the principles of School-Based Management (SBM). The School Operational Assistance (BOS) funds are used to support operational learning needs, procurement of infrastructure, teacher training, and other supporting activities that have a positive impact on improving the quality of learning. Challenges faced include limited funding, reliance on accountability reports, and coordination challenges among stakeholders. However, overall, the management of BOS funds at this school is effective and contributes significantly to supporting a quality learning process. This research contributes to the development of a quality-based BOS fund management model and serves as a reference for policymakers in improving the effectiveness of the BOS program, particularly in areas with unique characteristics such as Sigi. Keywords: BOS funds, management effectiveness, learning, Sukma Bangsa Sigi School.